2015
DOI: 10.1016/j.cmi.2014.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus aureus complex from animals and humans in three remote African regions

Abstract: Staphylococcus schweitzeri has been recently considered to be a highly divergent Staphylococcus aureus clade and usually colonises nonhuman primates and bats in sub-Saharan Africa. Its transmissibility to humans remains unclear. We therefore investigated the transmission of S. aureus and S. schweitzeri among humans, domestic animals, and wildlife in three remote African regions. A cross-sectional study on nasal and pharyngeal colonisation in humans (n = 1288) and animals (n = 698) was performed in Côte d'Ivoir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
84
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(87 citation statements)
references
References 27 publications
2
84
0
1
Order By: Relevance
“…However, Spa type t645, the second most frequent type in our collection (20.6%), also common in Western Europe and the Middle East (http://spaserver.ridom.de), was found to be the most frequent type isolated from SSI at Mulago National referral hospital [22], supporting the notion that there is a changing epidemiology reflected by community associated SCC mec genotypes being now more associated with hospital infections as observed elsewhere [23, 45]. However, it is noteworthy that some spa types of PVL+ S. aureus in the present study (t186, t729 and t355) have been previously identified in studies from Africa, and they all share the MLST type ST88 [46]. …”
Section: Discussionsupporting
confidence: 85%
“…However, Spa type t645, the second most frequent type in our collection (20.6%), also common in Western Europe and the Middle East (http://spaserver.ridom.de), was found to be the most frequent type isolated from SSI at Mulago National referral hospital [22], supporting the notion that there is a changing epidemiology reflected by community associated SCC mec genotypes being now more associated with hospital infections as observed elsewhere [23, 45]. However, it is noteworthy that some spa types of PVL+ S. aureus in the present study (t186, t729 and t355) have been previously identified in studies from Africa, and they all share the MLST type ST88 [46]. …”
Section: Discussionsupporting
confidence: 85%
“…It harbored the beta-lactamase operon as well as the IEC genes sea , sak and scn .CC6 has been recovered occasionally from humans including butchers [117] and it has been implicated in episodes of food-poisoning [118]. It was previously identified in camels from Dubai, where it carried a different sea allele [21], as well as in non-human primates and various domestic animals [4,119]. …”
Section: Resultsmentioning
confidence: 99%
“…CC15 is a widespread and common human lineage [120,121]. It has occasionally been reported from companion animals [124], primates [119] and mice [36]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While the progenitor molecule PRF-119 demonstrated activity against all clinical S. aureus isolates collected from multiple centers in a European country (3), the present study aimed at challenging the optimized bacteriophage endolysin HY-133 with isolates belonging to the S. aureus complex from sub-Sahara Africa, including the recently described species Staphylococcus schweitzeri (5,6). This species shows a peptidoglycan type which is distinct from that of S. aureus sensu stricto (5).…”
mentioning
confidence: 99%